The unfolding of Euro Area banks' profitability - Veríssimo, P.; Carvalho, P.; Laureano, L. (10th Portuguese Finance Network Conference, 2018)
In this paper, we analyze how bank-specific, industry-specific and macroeconomic determinants affect the profitability of 3,046 banks across 19 Euro area countries, from 2006 to 2015. We split our sample of Euro area banks into peripheral and core countries’ banks and include a significant number of unlisted banks, as they represent most banks in the European Union. Our results confirm the relevance of loan loss provisions, non-interest income share, cost-to-income ratio, total assets growth rate, deposit funding share, GDP growth and interest rates as important drivers of banks’ profitability, when all Euro area banks are analyzed together. In this respect, once eased the unconventional monetary policy measures, which stimulated a low interest rates environment for a long time, and a solution for the European non-performing loans problem is found, banks’ returns are likely to boost. Conversely, when peripheral and core countries’ banks are separately assessed, we find an asymmetric effect of some components between both groups. The loan loss provisions burden is, on average, at least 3 times larger in peripheral banks. Similarly, the impact of loan loss provisions on profitability levels during the 2008-2013 financial crisis period was significantly more severe in peripheral banks. Finally, our results suggest that the improvement of efficiency levels and higher bank concentration increase the returns of peripheral banks. In contrast, the positive effect of customer deposits suggests that core countries’ banks make better use of this source of funding.